An analysis of parliamentary intelligence oversight in South Africa with speciric reference to the Joint Standing Committee on intelligence - Hough, Mike (Michael) (University of Pretoria, 2013)
Dissertation (M (Political Sciences))--University of Pretoria, 2006.